An ethanol extract of Origanum vulgare attenuates cyclophosphamide-induced pulmonary injury and oxidative lung damage in mice. (October 2014) - Shokrzadeh, Mohammad; Ahmadi, Amirhossein; Chabra, Aroona; Naghshvar, Farshad; Salehi, Fatemeh; Habibi, Emran; Haghi-Aminjan, Hamed
Abstract Context: Injury to normal tissues is the major limiting side effect of using cyclophosphamide (CP), an antineoplastic alkylating compound. Objective: This study was undertaken to evaluate the protective effect of an extract of Origanum vulgare L. (Lamiaceae), an antioxidative medicinal plant, against CP-induced oxidative lung damage in mice. Materials and methods: Mice were pre-treated with various doses of O. vulgare extract (50, 100, 200, and 400 mg/kg) for 7 consecutive days followed by an injection with CP (200 mg/kg b.w.) One hour after the injection of O. vulgare on the last day, mice were injected with CP; 24 h later, they were euthanized, their lungs were immediately removed, and biochemical and histological studies were conducted. Results: A single dose of CP markedly altered the levels of several biomarkers associated with oxidative stress in lung homogenates. Pretreatment with O. vulgare significantly reduced the levels of lipid peroxidation and attenuated the alterations in glutathione content and superoxide dismutase activity induced by CP in lung tissue. In addition, O. vulgare effectively alleviated CP-induced histopathological changes in lung tissue. Conclusions: Our results revealed that O. vulgare protects lung tissues from CP-induced pulmonary damage and suggest a role for oxidative stress in the pathogenesis of lung disease produced by CP. Because O. vulgare has been extensively used as an additive agent and is regarded as safe, it may be used concomitantly as a supplement for reducing lung damage in patients undergoing chemotherapy.